Image-guided stent-directed irreversible electroporation for circumferential ablation in the rat esophagus - Kim, Song Hee; Jeong, Seung; Kang, Jeon Min; Park, Yubeen; Ryu, Dae Sung; Won, Dong-Sung; Kim, Ji Won; Zeng, Chu Hui; Kim, Hyung-Sik; Kim, Hong Bae; Lee, Sang Soo; Park, Jung-Hoon (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Irreversible electroporation (IRE) has been investigated in the alimentary tract; however, the lack of dedicated electrodes and insufficient tissue responses made its application limited. The aim of this study was to investigate the efficacy and safety of image-guided stent-directed IRE in the rat esophagus. Methods: The bipolar self-expandable electrode (SE) was developed using the braiding technique. A finite element analysis was performed to validate optimal electrical field strength for the rat esophagus. A total of 40 out of 50 rats received stent-directed IRE and were sacrificed at 10 h, 3 days, 7 days, and 28 days of 10 each. The remaining ten rats underwent a sham procedure. The outcomes of stent-directed IRE were assessed by esophagography and histological responses. Results: Stent-directed IRE was technically successful in all rats with mild muscle contraction. The heart rate dropped immediately and gradually recovered at 180 s. TUNEL and caspase-3 with submucosal thickness significantly increased at 10 h and Day 3 compared with those of the sham control (all p < 0.001). The thickness of epithelial layers with collagen deposition significantly decreased at 10 h and Day 3 (all p < 0.001), however, increased at Day 7 compared with that of the sham control (all p < 0.05). The Ki67-positive deposition significantly increased at Day 3 and 7 compared with that of the sham control (all p < 0.001). All variables were similar to those of the sham control at Day 28. Conclusion: Image-guided stent-directed IRE was effective and safe in the rat esophagus. It seems to have effectively and evenly induced cell death and gradually recovered with cellular regeneration.